Re-examination of Australian and Oriental species of Minagenia Banks, 1934 (Hymenoptera: Pompilidae), with a new record for the genus in Australia and a new species description - Decker, Brenna L.; Pitts, James P.; Yuan, David; Rodriguez, Juanita (Zootaxa, 2020)
The genus Minagenia Banks, 1934 is reported for the first time from Australia. A new species, M. lasallei Decker, Rodriguez & Pitts, sp. nov. (Australia: from Queensland to Tasmania), is described and illustrated. A key to the four species from the Australasian and Oriental regions is given. Three species are removed from Asian Minagenia: granulosa Tsuneki, 1989, comb. nov., to the genus Priocnemis Schiødte, 1837; pempuchiensis Tsuneki, 1989, comb. nov., to the genus Nipponodipogon Ishikawa, 1965; and assimilis Smith, 1861, comb. nov., to the genus Dichragenia Haupt, 1950. Minagenia alticola Tsuneki, 1989 is a member of an undescribed genus. Placement of this species is maintained in Minagenia until the new genus can be described in a future work. Minagenia brevicornis (Banks, 1934) is redescribed.